Efeitos subletais de agrotóxicos utilizados em meloeiro (Cucumis melo L.) sobre Chrysoperla genanigra Freitas (NEUROPTERA: CHRYSOPIDAE) - Lima, Alricélia Gomes de (Universidade Federal Rural do Semi-Árido, 2018)
The melon (Cucumis melo L.) is one of the crops that receive the most applications of chemical insecticides and this is due to its economic importance, represented by its great productive potential in the Northeast region, which suffers from phytosanitary problems due to the attack of harmful insects and harmful to culture. The intensive use of non-selective chemicals ends up causing harm to the environment, helping to eliminate the natural enemies. In this way the demand for alternative becomes indispensable to minimize the damages due to the excessive use of these products. Integrated Pest Management (IPM) encourages good agricultural management practices by making use of pest control techniques through the use of biological control agents. Chrysoperla genanigra is a polyphagous predator, with wide geographic distribution, great search efficiency, considered a great alternative to the use of chemicals. As a result, the experimental work evaluated the selectivity of commercially used insecticides for pest suppression in the melon crop, applied to the first larval instar of the C. genanigra predator, contributing to the categorization of the products in classes of toxicity recommended by the IOBC. Adult chrysopedes were collected in orchards at the Ufersa farm in maize plantations to create maintenance in laboratory conditions. The selectivity test was conducted at the Laboratory of Chemical Selectivity of the Plant Protection Sector of the Federal Rural Semi-Arid University (UFERSA), on first instar larvae, up to 24 hours old from the mass establishment. The experimental design was a completely randomized design consisting of eight treatments: seven chemical products: azadirachtin (0.036 g ai / L), deltamethrin (0.0075 g ai / L), spinetoram (0.08 g ai / L), acetamiprid (0.06 g ai / L), chlorantraniliprole (0.015 g ai / L), pyriproxyfen + xylene (0.1 + 0.8 g ai / L), lambdacyhalothrin and a witness consisting of distilled water). Each treatment made use of thirty larvae, kept individually in petri dishes and exposed to the dry residues of each insecticide. The applications were performed with the assistance of a manually pressurized sprayer (1.5 ± 0.5 mg of chemical syrup / cm 2) on the petri dishes. After application, the specimens were kept in an air conditioned room at 25 ± 2 ° C, RH of 60 ± 10% and photophase of 12 hours. The parameters evaluated were mortality, duration of each instar, pupal survival, sexual ratio, fecundity, as well as the viability of the eggs produced by the adults from the insects tested in the bioassay. By the calculation of the total effect, the products were classified into toxicity classes (IOBC): Azadirachtin (tetranostriperoids), espinetoram (spiny), acetamiprid (neonicotinoid), chlorantraniliprole (antranilamide), priproxifem (pyridyloxypropyl ether) and lambda cyhalothrin, were classified as harmful (class 4) and deltamethrin (pyrethroid) was the only considered slightly harmful (class 2) to the first instar larva stage of the C. genanigra species.
Monografia
Keywords: MIP; Controle biológico; Inseticidas; Predador; Crisopídeos; IPM; Biological control; Insecticide; Predator; Green lacewings; CIENCIAS AGRARIAS::AGRONOMIA